2019
DOI: 10.1039/c8sc04162h
|View full text |Cite
|
Sign up to set email alerts
|

Ni-catalyzed migratory fluoro-alkenylation of unactivated alkyl bromides with gem-difluoroalkenes

Abstract: A migratory fluoro-alkenylation of unactivated alkyl bromides is reported; the reaction is enabled by fluorine effects and involves an alkyl nickel chain-walking mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(33 citation statements)
references
References 65 publications
0
33
0
Order By: Relevance
“…In addition, reaction of vinyl fluoride 70 led to the formation of vinyl boronic ester 71 . Since direct cross coupling with vinyl fluorides is slow at ambient temperatures, it is suggested that the product formation occurs via 1,2‐elimination of the corresponding alkyl‐[Ni]‐complex . With respect to the mechanistic proposal for the reaction in toluene, it was observed that use of α‐methyl styrene ( 72 ) led to products resulting from a Heck‐type reaction ( 74 ) and hydroarylation ( 75 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, reaction of vinyl fluoride 70 led to the formation of vinyl boronic ester 71 . Since direct cross coupling with vinyl fluorides is slow at ambient temperatures, it is suggested that the product formation occurs via 1,2‐elimination of the corresponding alkyl‐[Ni]‐complex . With respect to the mechanistic proposal for the reaction in toluene, it was observed that use of α‐methyl styrene ( 72 ) led to products resulting from a Heck‐type reaction ( 74 ) and hydroarylation ( 75 ).…”
Section: Methodsmentioning
confidence: 99%
“…gem-Difluoroalkenes reacted with CO 2 in the presence of alkenylboronic acid pinacol esters using a Cu I -based catalyst system and Xantphos as a ligand to afford a variety of valuable α-fluoroacrylic acids and α-fluoroacrylates (20, Scheme 6). [15] This one-pot formal ipso monocarboxylation of the CÀ F bond occured with high (Z)-selectivity and probably involved fluorinated boronate esters (19) as the key intermediate.…”
Section: Borylation and Silylationmentioning
confidence: 97%
“…A regio‐ and stereoselective convenient nickel‐catalyzed reductive coupling reaction of unactivated alkyl bromides with gem ‐difluoroalkenes generates α ‐benzyl fluoroalkenes (Scheme ) . This reaction delivered diversely functionalized monofluoroalkenyl derivatives ( 40 ) through a distinctive catalytic cycle that combined alkyl−Ni chain‐walking with defluorinative coupling.…”
Section: Reactions Proceeding Via β‐Fluoride Eliminationmentioning
confidence: 99%
“…Inspired by a series of related Ni‐catalyzed remote functionalization techniques with a different set of electrophilic partners, Feng's group recently described the means to forge C−C bonds by combining unactivated alkyl bromides with gem ‐difluoroalkenes as coupling counterparts (Scheme ) . As for Zhu and Yin's protocols, the reaction took place at the benzylic sp 3 C−H site.…”
Section: Ni‐catalyzed Remote Sp3 Functionalizationmentioning
confidence: 99%